2006
DOI: 10.4049/jimmunol.177.11.7889
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocytoplasmic Shuttling of HMGB1 Is Regulated by Phosphorylation That Redirects It toward Secretion

Abstract: The high mobility group box 1 (HMGB1) protein can be secreted by activated monocytes and macrophages and functions as a late mediator of sepsis. HMGB1 contains two nuclear localization signals (NLSs) for controlled nuclear transport, and acetylation of both NLSs of HMGB1 is involved in nuclear transport toward secretion. However, phosphorylation of HMGB1 and its relation to nuclear transport have not been shown. We show here that HMGB1 is phosphorylated and dynamically shuttled between cytoplasmic and nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
335
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 315 publications
(345 citation statements)
references
References 41 publications
7
335
1
2
Order By: Relevance
“…And it is safe to say that post translational modifications play an important role in the nucleocytoplasmic redistribution. As mentioned above, oxidation, hyperacetylation and phosphorylation of HMGB1 contribute to its cytoplasmic relocation in inflammatory and cancer cells (Hoppe et al, 2006;Youn et al, 2006;Tsung et al, 2007;Kang et al, 2009;Evankovich et al, 2010;Lee et al, 2012). Experiments in Schistosoma mansoni conclusively demonstrated that acetylation and phosphorylation played roles in cellular trafficking, culminating with its secretion to the extracellular milieu de Abreu da Silva et al, 2011).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…And it is safe to say that post translational modifications play an important role in the nucleocytoplasmic redistribution. As mentioned above, oxidation, hyperacetylation and phosphorylation of HMGB1 contribute to its cytoplasmic relocation in inflammatory and cancer cells (Hoppe et al, 2006;Youn et al, 2006;Tsung et al, 2007;Kang et al, 2009;Evankovich et al, 2010;Lee et al, 2012). Experiments in Schistosoma mansoni conclusively demonstrated that acetylation and phosphorylation played roles in cellular trafficking, culminating with its secretion to the extracellular milieu de Abreu da Silva et al, 2011).…”
Section: Discussionmentioning
confidence: 92%
“…Later, it has been demonstrated that decreased histone deacetylases(HDACs) activity in hepatocytes, following ischemia and reperfusion, was a mechanism that promoted hyperacetylation and secretion of HMGB1 (Evankovich et al, 2010). In addition, several investigations demonstrated that HMGB1with phosphorylation at specific serine residues of nuclear localization signals (NLS) regions was transported to cytoplasm, and subsequently secreted from cells (Youn et al, 2006;Kang et al, 2009;Lee et al, 2012). Hence, it is safe to say that post translational modifications (PTMs) play a critical role in governing the nucleocytoplasmic shuttling of HMGB1.…”
Section: Introductionmentioning
confidence: 99%
“…Park, Gwanju Institute of Science and Technology, Gwanju, South Korea) (30) was used for the aggregation study. Myc-tagged wild-type HMGB1 as well as HMGB1 boxes A (aa 1-79) and B (aa 88-162) plasmids were used for the transfection study (31,32). We used recombinant HMGB1 (rHMGB1) proteins produced in insect High Five cells (Insect HMGB1; ATGen), a mouse myeloma cell line of NS0 (R&D Systems), or human cells (Euk HMGB1; Sino).…”
Section: Cell Culture and Dna Transfectionmentioning
confidence: 99%
“…Chinese hamster lung fibroblast O23 cells were transiently transfected with luciferase plasmid of pRSVLL/V and HMGB1 plasmid (31,34). pRSVLL/ V encoding cytoplasmic luciferase plasmid (a kind gift from Dr.…”
Section: In Vivo Refolding Assaymentioning
confidence: 99%
“…As indicated by in vitro studies, HMGB1 can exit cells in at least two distinct settings: activation and death. During activation of macrophages by LPS, TNF-␣, and other stimulating agents, HMGB1 translocates from the nucleus to the cytoplasm following acetylation, which alters its intracellular trafficking and location; phosphorylation may also affect this event (7,8). In the cytoplasm, HMGB1 moves into vesicles from which it can be secreted.…”
mentioning
confidence: 99%